Shunt Active Power Filter Employing Kalman Filter Estimator For Harmonics Reduction - Abu Hasim, Ahmad Shukri (UTeM, 2016)
The wide use of non-linear loads, such as front-end rectifiers connected to the power distribution systems for DC supply or inverter-based applications, causes significant power quality degradation in power distribution networks in terms of current or voltage harmonics, power factor, and resonance problems. Many techniques have been proposed by the researchers to overcome these problems. One of the method is by using shunt active power filter (APF). This technique is an effective solution for reducing the current harmonics for low to medium power applications. Therefore, this research is targeted to design and implement a three-phase shunt APF employing Kalman filter estimator. The first step is designing the shunt APF circuit by deploying voltage source inverter (VSI). However, when using VSI the DC voltage needs to be maintained because its influence the real power conversion hence degrades the performance of the APF. Two methods are used to overcome this problem namely are conventional PI and PI-improved method. Both methods have been simulated under voltage variation and open circuit test. The results show that PI-improved voltage regulator produce better performance in reduction of the THD as the results reduce the surge current. On the other hands, three common controllers of the shunt APF for generation of reference current are compared and analysed to determine the best performance of THD reduction. Based on the results, the d-q reference current generator produces the lowest THD among others. Conventionally, low-pass filter (LPF) is used to filter out the unwanted DC component of the non-linear load to produce the sinusoidal waveform called reference current. However, when applying LPF it contribute with the phase shift and high transient at the supply current. Therefore, to reduce these problems, the digital Kalman filter estimator is used to replace the LPF for generating the reference current. Details investigation between conventional and proposed method under simulation based on Matlab simulink platform and experimental are made for three types of load namely three-phase rectifier with R-load, three-phase rectifier with RC-load and three-phase induction motor are presented. The performance criteria of the shunt APF are determined by the supply current waveform, THD, harmonics spectrum and power quality measurements were also obtained by simulation and experimental. In conclusion, by employing Kalman filter estimator for generating the reference current it reduce the time delay and high transient current at the power supply thus, improved the overall THD from 0.15% to 0.42% compared to the LPF.